Extreme Philately : The Most Unusual Stamps of the World Part 3 - Gee, Genevieve V. A.; Das, Indraneil (2020)
This is the third part (see Gee and Das 2019a, 2019b) of unusual stamps of the world, featuring postage stamps made of resin, are textured through thermography, are plasticcoated, or with foils of platinum, gold, silver, gun metal or are minted in silver or have embedded goldore. Also included are embossed stamps, flocked paper stamps (that produce the effect of fur, wool, skin or the delicate texture of flower petals), Braille stamps, vinyl record stamps, including the first “talking” stamps that play on a gramaphone, CD-ROM stamps as well as stamp pasted on CD-ROM,DVD ROM Stamps, multimedia stamps, including one that uses a specially-made pen that acts as infrared reading system, stamps with augmented reality, including Bee Tagg, or those, when scanned with an app or QR code, play high-definition films or show hidden images, stamps printed with thermochromatic ink, that, when warmed bytouch, reveal images or words, and associated with solving games and mysteries.